Elvitegravir, cobicistat, emtricitabine and tenofovir alafenamide for the treatment of HIV in adults. (11th February 2016) - Bonora, Stefano; Calcagno, Andrea; Trentalange, Alice; Di Perri, Giovanni
ABSTRACT: Introduction : Tenofovir alafenamide (TAF) is is a novel tenofovir prodrug with a 90% reduction in plasma tenofovir concentrations as compared to tenofovir disoproxil fumarate (TDF) and such property suggests that TAF-containing regimens can improve renal and bone safety compared with TDF-containing regimens. Single tablet regimen elvitegravir/cobicistat/emtricitabine/TAF (E/C/F/TAF) is the first coformulation that includes TAF in place of TDF. This review aims to provide an overview of its role in the treatment of HIV infection. Areas covered : This review covers pre-clinical and clinical data serached through Medline and Pubmed up to August 2015. Expert opinion : In terms of efficacy, E/C/F/TAF was found to be non inferior to E/C/F/TDF in naive patients, and more effective in patients switching from TDF-based regimens with efavirenz or boosted PI. In safety analyses, E/C/F/TAF was constantly found to be associated with significant improvement of renal function and urinary markers of proximal tubulopathy, and significant improvement of bone mineral density (BMD) as compared to TDF-containing regimens. E/C/F/TAF, as a new single tablet regimen, appeared to be promising for optimization of cART tolerability in HIV-infected patients.